46XX pure gonadal dysgenesis with dysgerminoma along with leydig cells: a unique presentation - Tak, Apoorva; Singh, Pratibha; Yadav, Garima; Rao, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Authors report a unique case of 46XX gonadal dysgenesis, with dysgerminoma in one ovary and other streak ovary with hilar nests of leydig cells. It is exceptionally rare to find dysgerminoma in a dysgenetic gonad with no Y chromosome and so is the presence of leydig cells in the contralateral streak ovary in a patient with 46XX pure gonadal dysgenesis.